Effects of sodic water irrigation on growth, physiological relations and ion uptake in two Ziziphus rootstocks - SINGH, ANSHUMAN; KUMAR, ASHWANI; RAJKUMAR, RAJKUMAR; SHEORAN, PARVENDER; YADAV, R K (The Indian Journal of Agricultural Sciences, 2018)
We studied the effects of sodic irrigation on growth, physiological parameters and mineral partitioning in Zizyphus rotundifolia (ZR) and Z. spina-christi (ZS) seedlings used as rootstocks for Indian jujube scion cultivars. Plants grown in normal soils were irrigated with fresh (control) and three kinds of sodic waters having residual sodium carbonate (RSC) levels of 3, 6 and 9 meq/l. Both the species displayed appreciable decreases in fresh and dry weights of shoots and roots at RSCiw level of 9 meq/l. Leaf chlorophyll and chlorophyll fluorescence also decreased with increasing sodicity. While leaf proline content remained unchanged up to RSCiw 3 meq/l, plants treated with 9 meq/l sodic water had nearly twofold higher leaf proline than control indicating that it could play a major role in osmotic adjustment in salt stressed plants. Na+ and Cl- contents increased while K+ and Ca2+ declined in different plant parts with increase in RSCiw. Na+: K+ ratio was higher at a given RSCiw in leaves and roots of ZS and in stems and roots of ZR reflecting better Na+ exclusion by ZR. ZR leaves also had less Cl- than ZS at a given RSCiw. Owing to these adaptive traits, both the species could tolerate RSCiw up to 6 meq/l.